Hydrodynamic instability experiments with three-dimensional modulations at the National Ignition Facility. (2015) - Smalyuk, V.A.; Weber, S.V.; Casey, D.T.; Clark, D.S.; Field, J.E.; Haan, S.W.; Hamza, A.V.; Hoover, D.E.; Landen, O.L.; Nikroo, A.; Robey, H.F.; Weber, C.R.
Abstract : The first hydrodynamic instability growth measurements with three-dimensional (3D) surface-roughness modulations were performed on CH shell spherical implosions at the National Ignition Facility (NIF) [G. H. Miller, E. I. Moses, and C. R. Wuest, Opt. Eng.43, 2841 (2004)]. The initial capsule outer-surface amplitudes were increased approximately four times, compared with the standard specifications, to increase the signal-to-noise ratio, helping to qualify a technique for measuring small 3D modulations. The instability growth measurements were performed using x-ray through-foil radiography based on time-resolved pinhole imaging. Averaging over 15 similar images significantly increased the signal-to-noise ratio, making possible a comparison with 3D simulations. At a convergence ratio of ${\sim}2.4$, the measured modulation levels were ${\sim}3$ times larger than those simulated based on the growth of the known imposed initial surface modulations. Several hypotheses are discussed, including increased instability growth due to modulations of the oxygen content in the bulk of the capsule. Future experiments will be focused on measurements with standard 3D 'native-roughness' capsules as well as with deliberately imposed oxygen modulations.